ART AND ABDUCTION WITHIN UMBERTO ECO’S THEORETICAL WORKS - Junior, Antonio Barros de Brito (Laboratório Editorial FCL-UNESP, 2010)
This article deals with the concept of abduction within Umberto Eco's theoretical work. The main goal of this text is to show how Umberto Eco disdains the aesthetic component in favor of a more cognitive approach of artistic fruition. Besides, the article intends to show the relationship between abduction and the Kantian concept of teleological judgment. It also offers, as a conclusion, an analysis of some of the consequences of this relationship which Umberto Eco was not totally aware of.